Human Security Psychology: A Linking Construct for an Eclectic Discipline. Issue 2 (June 2023) - Hodgetts, Darrin; Hopner, Veronica; Carr, Stuart; Bar-Tal, Daniel; Liu, James H.; Saner, Raymond; Yiu, Lichia; Horgan, John; Searle, Rosalind H; Massola, Gustavo; Hakim, Moh A.; Marai, Leo; et al.
Since its inception as a modern and evolving discipline, psychology has been concerned with issues of human security. This think piece offers an initial conceptualisation of human security as a broad security concept that encompasses a range of interrelated dimensions that have been responded to by different sub-disciplinary domains within psychology. We advance an argument for a human security psychology as a connecting focal point for general psychology that enables us to bring knowledge from across our eclectic discipline into further dialogue. This is a necessary step in understanding better the state of current thinking on the psychology of security and as a basis for informing further theory, research and practice efforts to address issues of human (in)security. This initial effort is informed by Assemblage Theory, which offers a dynamic and contextually rich perspective on people as agentive beings entangled within evolving natural and social formations that can foster or undermine their experiences of [in]security. The article is completed with a brief agenda for advancing human security psychology.